2002
DOI: 10.1002/hipo.10049
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of novel picture pairs activates the perirhinal cortex: An fMRI study

Abstract: It is well established in nonhuman primates that the medial temporal lobe (MTL) structures, the hippocampus and the entorhinal and perirhinal cortices, are necessary for declarative memory encoding. In humans, the neuropathological and neuropsychological changes in early Alzheimer's disease (AD) further support a role for the rhinal cortex in the consolidation of new events into long-term memory. Little is known, however, regarding the function of the rhinal cortex in humans in vivo. To examine the participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 71 publications
4
39
1
Order By: Relevance
“…Our memory task evoked less position-related activity than object-related activity throughout the MTL in young subjects; whereas other studies have suggested greater activity in some MTL regions during spatial than object processing (Buffalo et al, 2006;Mitchell et al, 2000;Pihlajamäki et al, 2003Pihlajamäki et al, , 2004Pihlajamäki et al, , 2005. Our spatial memory task was relatively simple, perhaps evoking only low-level spatial memory processing in the MTL.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our memory task evoked less position-related activity than object-related activity throughout the MTL in young subjects; whereas other studies have suggested greater activity in some MTL regions during spatial than object processing (Buffalo et al, 2006;Mitchell et al, 2000;Pihlajamäki et al, 2003Pihlajamäki et al, , 2004Pihlajamäki et al, , 2005. Our spatial memory task was relatively simple, perhaps evoking only low-level spatial memory processing in the MTL.…”
Section: Discussioncontrasting
confidence: 56%
“…A number of studies have demonstrated that the medial temporal lobe (MTL) region is crucial for episodic memory function and related working memory functions (Campo et al, 2005;Habeck et al, 2005;Hannula and Ranganath, 2008;Hayes et al, 2004;Piekema et al, 2006;Ranganath et al, 2004;Yonelinas et al, 2007). In the MTL, distinct subregions have been shown to make different contributions to object and spatial memory processes (Pihlajamäki et al, 2003(Pihlajamäki et al, , 2004(Pihlajamäki et al, , 2005, in the binding of object and spatial information (Mitchell et al, 2000), in encoding and retrieval (de Zubicaray et al, 2001;Kirwan and Stark, 2004;Tsukiura et al, 2005), as well as in familiarity and recognition judgments (Daselaar et al, 2006;Gonsalves et al, 2005;Henson, 2005;Henson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous blocked design studies have found similar activation (regardless of subsequent memory) during intentional encoding of pairs of unrelated visual stimuli in the right parahippocampal gyrus and right hippocampus (Henke et al, 1997) and bilateral parahippocampal gyrus and hippocampus (Rombouts et al, 1997;Pihlajamaki et al, 2003). A more recent event-related fMRI study observed encoding success activity in right parahippocampal gyrus associated with correct perceptual source judgments relative to semantic source judgments, again under intentional encoding instructions (Prince et al, 2005).…”
Section: Encoding Success Activitymentioning
confidence: 73%
“…Each of these topics will be addressed in more detail later, in addition to a brief discussion of the current results in relation to Multiple Trace Theory (MTT) Moscovitch, 1997, 1998;Nadel et al, 2003). , 1997) and bilateral parahippocampal gyrus and hippocampus (Rombouts et al, 1997;Pihlajamaki et al, 2003). A more recent event-related fMRI study observed encoding success activity in right parahippocampal gyrus associated with correct perceptual source judgments relative to semantic source judgments, again under intentional encoding instructions (Prince et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…Although neuroimaging studies in healthy subjects have shown that the medial temporal lobe (MTL) contributes to both long-term (Milner et al, 1998;Pihlajamäki et al, 2003, Squire et al, 2004) and short-term memory (Ranganath and D'Esposito, 2001;Hannula et al, 2006;Axmacher et al, 2008), the nature of the specific MTL contributions to short-to long-term memory remains unclear. Recently, James et al (2009) explored this question in a high-density event-related potentials (ERP) study, in which healthy subjects performed a continuous recognition task of meaningful drawings.…”
Section: Introductionmentioning
confidence: 99%